Building serverless Python web services with Zappa : build and deploy serverless applications on AWS using Zappa - Barguzar, Abdulwahid Abdulhaque (Packt Publishing, 2018)
Serverless applications are quite popular, not just because they save developers the trouble of managing servers, but also because they provide several other benefits such as cutting heavy costs and improving the overall performance of the application. This book will teach you the fundamentals of creating efficient serverless applications.